Evaluasi Pelaksanaan Pemungutan, Prosedur Pencatatan dan Monitoring Realisasi Penerimaan PBB-P2 - Deddy Priyatna; Umar Yeni Suyanto; Cuk Triono Singgih; Rita Nataliawati; Isna Ayu Safitri Kusuma Dewi (Journal of Trends Economics and Accounting Research, 2023)
This research aims to gain knowledge regarding how collection is carried out, recording procedures and monitoring the realization of PBB-P2 revenues in Lamongan Regency. This research was carried out at the Lamongan Regency Regional Revenue Agency. The method in this research uses qualitative methods using primary and secondary data sources obtained through documentation, observation and interviews. In data analysis, data reduction is used and data validation uses source, time and technique triangulation. Research results The implementation of PBB-P2 collection is effective, The recording procedure is systemized and uses the SiPaLin and Sakti applications, Monitoring activities have an influence on the realization of PBB-P2 revenue. In carrying out the collection, BAPENDA has opened an online payment service. The recording procedure is in line with PP No. 71 of 2010 concerning SAP, the recording system uses 2 software systems, namely SiPaLin and Sakti. Monitoring activities are carried out through feedback on the realization of revenues from sub-districts and also providing rewards/gifts to sub-district or village heads who successfully pay according to certain criteria and also providing fines for any late payment of PBB-P2 tax.